2014
DOI: 10.1371/journal.pone.0091419
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Taphonomy, Taphofacies, and Bonebeds of the Mio-Pliocene Purisima Formation, Central California: Strong Physical Control on Marine Vertebrate Preservation in Shallow Marine Settings

Abstract: BackgroundTaphonomic study of marine vertebrate remains has traditionally focused on single skeletons, lagerstätten, or bonebed genesis with few attempts to document environmental gradients in preservation. As such, establishment of a concrete taphonomic model for shallow marine vertebrate assemblages is lacking. The Neogene Purisima Formation of Northern California, a richly fossiliferous unit recording nearshore to offshore depositional settings, offers a unique opportunity to examine preservational trends a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 96 publications
(201 reference statements)
1
48
0
Order By: Relevance
“…This pattern of attrition and abrasion is typical of reworked bone material in other phosphorite bone accumulations (Walsh & Martill, ; Boessenecker et al. ), suggesting the specimen was reworked prior to redeposition in a phosphatic lag deposit.…”
Section: Revised Description Of the Cranial Osteology Of Cerebavis Cementioning
confidence: 58%
See 1 more Smart Citation
“…This pattern of attrition and abrasion is typical of reworked bone material in other phosphorite bone accumulations (Walsh & Martill, ; Boessenecker et al. ), suggesting the specimen was reworked prior to redeposition in a phosphatic lag deposit.…”
Section: Revised Description Of the Cranial Osteology Of Cerebavis Cementioning
confidence: 58%
“…However, more severe attritional damage and rounding through abrasion is apparent in the caudal region of the skull (see below). This pattern of attrition and abrasion is typical of reworked bone material in other phosphorite bone accumulations (Walsh & Martill, 2006;Boessenecker et al 2014), suggesting the specimen was reworked prior to redeposition in a phosphatic lag deposit.…”
Section: Revised Description Of the Cranial Osteology Of Cerebavis Cementioning
confidence: 64%
“…This helps to explain the abundance of decimeter-scale coprolites and other vertebrate fossils, while smaller fossils such as shark teeth were likely removed by wave currents. Boessenecker et al (2014) also reported a preservation bias against shark teeth in certain facies of the Purisima Formation of California, which includes phosphatic bonebeds of similar lithology and paleoenvironment to those at Mali-8.…”
Section: Interpretation Of Feeding Tracesmentioning
confidence: 96%
“…Prior models of lag deposit formation during the Late Cretaceous and Cenozoic of North America indicate that many concentrations of vertebrate fossils occur at the boundary between third order sea level cycles (e.g., [34][35][36][37][38][39][40][41][42][43]). These sea level cycles can be recognized in outcrop by disconformities and lag deposits that occur along geologic contacts between clay-dominated and sand or limestone dominated lithologies (e.g., [44][45][46]). Vertebrate fossils concentrated in these lags can differ on the order of several million years and represent organisms with different habitat preferences (e.g., [37,46,47]).…”
Section: Third Order Sea Level Generated Lag Depositsmentioning
confidence: 99%
“…These sea level cycles can be recognized in outcrop by disconformities and lag deposits that occur along geologic contacts between clay-dominated and sand or limestone dominated lithologies (e.g., [44][45][46]). Vertebrate fossils concentrated in these lags can differ on the order of several million years and represent organisms with different habitat preferences (e.g., [37,46,47]).…”
Section: Third Order Sea Level Generated Lag Depositsmentioning
confidence: 99%